Acardiac – Acephalus Twin – A Rare Case Report and Review of Literature - Mukta Mital (International Journal of Recent Surgical and Medical Sciences, 2015)
Acardiac twin pregnancy is a rare complication of monochorionic twinning caused by aterioarterial and venovenous placental anastomosis, leading to circulatory predominance of one twin (1). The donor “pump’ twin provides circulation for itself as well as and for the recipient acardiac twin. The acardiac twin is usually grossly abnormal with severe reduction anamolies of the upper part of the body. We present a case of acephalus acardiac anomaly diagnosed by ultrasound, with subsequent post delivery followup.